The effect of 10 days of heat acclimation on exercise performance in acute hypobaric hypoxia (4350 m). Issue 1 (2nd January 2016) - White, Ailish C.; Salgado, Roy M.; Astorino, Todd A.; Loeppky, Jack A.; Schneider, Suzanne M.; McCormick, James J.; McLain, Trisha A.; Kravitz, Len; Mermier, Christine M.
ABSTRACT: To examine the effect ("cross-tolerance") of heat acclimation (HA) on exercise performance upon exposure to acute hypobaric hypoxia (4350 m). Eight male cyclists residing at 1600 m performed tests of maximal aerobic capacity (VO2max ) at 1600 m and 4350 m, a 16 km time-trial at 4350 m, and a heat tolerance test at 1600 m before and after 10 d HA at 40°C, 20% RH. Resting blood samples were obtained pre-and post- HA to estimate changes in plasma volume (ΔPV). Successful HA was indicated by significantly lower exercise heart rate and rectal temperature on day 10 vs. day 1 of HA and during the heat tolerance tests. Heat acclimation caused a 1.9% ΔPV, however VO2max was not significantly different at 1600 m or 4350 m. Time-trial cycling performance improved 28 sec after HA (p = 0.07), suggesting a possible benefit for exercise performance at acute altitude and that cross-tolerance between these variables may exist in humans. These findings do not clearly support the use of HA to improve exercise capacity and performance upon acute hypobaric hypoxia, however they do indicate that HA is not detrimental to either exercise capacity or performance.